Regulation of peroxisome biogenesis and proliferation: characterization of Pex16p and Pex11pβ - Cardoso, Maria João Ribeiro (2015)
Peroxisomes are multifunctional organelles involved in various metabolic processes. The numerous severe disorders lead by peroxisomal malfunction in addition to the increasing evidences of the involvement of peroxisomes in several pathologies, from neurodegeneration to cancer and viral infection, renders this organelle an essential role for human health and development. Furthermore, peroxisomes are highly dynamic, adjusting their protein content, morphology and number in response to cellular needs. Peroxisome dynamics and their proper regulation are closely linked to organelle function and thus, human well-being. So that the study of the mechanisms that regulate peroxisomal biogenesis and proliferation is primordial. Being reversible phosphorylation a major intracellular control mechanism in eukaryotes with PP1 as the prominent player in dephosphorylation events, it is very likely that it represents an important regulation mechanism also in peroxisomes. As a matter of fact, some evidences in that direction have emerged, although they are still very scarce and mostly not for human cells. Interestingly, a large-scale blot screen on rat peroxisomes revealed the presence of several kinases and phosphatases, being PP1 one of them. The main goal of this thesis was to study the role of reversible phosphorylation in human peroxisomes through a very likely PP1 regulator, Pex16p, and a putative phosphorylated protein, Pex11pβ. Pex16p and Pex11pβ are essential players in the peroxisome biogenesis, elongation and division. Our studies were not able to verify a putative interaction between PP1 and Pex16p. S11 and S38 residues of Pex11pβ have also been demonstrated to not be involved in its regulation by putative phosphorylation. The regulation by key cysteines in Pex11pβ was also investigated, revealing that C18, C25 and C85 are apparently not involved in such mechanism. A possible role for an intriguing glycine-rich stretch in the intraperoxisomal region of Pex11pβ was also studied, with inconclusive results, being that it appears to be dispensable for Pex11pβ-driven peroxisomal growth and division. Our study also focused on the Pex11pβ N-terminally located amphipathic helices, reveling Helix 2 as essential for peroxisomal membrane elongation, with a probable involvement in the Pex11pβ dimerization process. Although with several negative results, our study opened some doors towards a better understanding of the mechanisms that regulate peroxisome biogenesis and proliferation. New protein-protein interaction methods which developed meanwhile may be useful to verify the likely transient PP1-Pex16p interaction. Moreover, we verified that other peroxins have putative PP1-binding motifs, representing possible further interconnectors between intracellular signal transduction and peroxisomes. Concerning Pex11pβ mechanisms of action and regulation, our study raised the hypothesis that other domains are involved in the elongation function since we demonstrated that N-terminal region in not sufficient to promote peroxisomal membrane elongation. We also propose that the inter-transmembrane domains area may be at least partially embedded within the lipid bilayer, defying the preconceived topology of this region of Pex11pβ. We further propose that other phosphorylation- and key cysteinesdriven Pex11pβ regulation is still an open field since that other residues present as potentially active in such processes. Our study brought valuable insights in the mysterious regulation mechanisms of peroxisomes, essential organelles for cellular function, with serious consequences for human health.